The cooperative experience as editorial moment in the cultural field - Nicolás Gómez Núñez; Carrera de Sociología de la Facultad de Educación y Ciencias Sociales de la Universidad Central de Chile; Rocio Mieres; Investigadora independiente; Camilo Lazo; Carrera de Sociología Universidad de Chile; Camila Hidalgo; Carrera de Sociología de la Universidad de Central de Chile; Dafne Jaime; Carrera de sociología de la Universidad de Chile; Gabriela Rojas; Investigadora independiente; Hernán Gajardo; Investigador independiente; Pablo Rojas; Investigador independiente (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2020)
The article shows the main results of a study on the views of members of the cooperative La Furia editors, when they reflect on the experiences of maintaining their collective action in the chilean cultural field. At the conceptual level, Becker's art world categories and Bourdieu's cultural field categories allowed us to explore the conventions that arise from the relations of technical assistance, associated work, reciprocity, diffusion and government of the cooperative. The research was carried out between 2017 and 2019, it used the qualitative methodology taking procedures from the grounded theory and the case study, it used the semi-structured interview and the observation of book fairs and the digital supports of the editorials of the cooperative La Furia; and we worked with content and social network analysis. Among the results is a description of the stages of the cooperative, the shared knowledge about the cooperative work and two dimensions that are manifested in a similar way among the publishers: working community and knowing how to edit.